2020
DOI: 10.1111/ppc.12588
|View full text |Cite
|
Sign up to set email alerts
|

Determining care burden and psychiatric symptom level in caregiver of schizophrenia patient

Abstract: Purpose: The present study was conducted to determine the care burden and psychiatric symptom levels of the caregivers of schizophrenic patients.Design and Methods: The caregivers of schizophrenic patients were included in this descriptive study.Findings: It was determined that there was a statistically significant difference in the care burden scores and the education, family type, and the presence of physical diseases of the caregivers (P < .05). It was determined that there was a statistically significant p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…34 It has been suggested that interventions that decrease the burden of care during the treatment of psychotic disorders should be a part of the treatment program. 15,16,32,32,33 Studies have shown that the burden of disease may be associated with symptoms of anxiety and depression. 29,35 In a study conducted by Vadher et al, 29 the caregivers of patients with schizophrenia were more likely to have depression, anxiety, and poor QoL when the burden of care was higher.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…34 It has been suggested that interventions that decrease the burden of care during the treatment of psychotic disorders should be a part of the treatment program. 15,16,32,32,33 Studies have shown that the burden of disease may be associated with symptoms of anxiety and depression. 29,35 In a study conducted by Vadher et al, 29 the caregivers of patients with schizophrenia were more likely to have depression, anxiety, and poor QoL when the burden of care was higher.…”
Section: Discussionmentioning
confidence: 99%
“…In studies that have reported on follow‐up periods, family interventions also improve family functioning in the longer term, with significant effects 34 . It has been suggested that interventions that decrease the burden of care during the treatment of psychotic disorders should be a part of the treatment program 15,16,32,32,33 …”
Section: Discussionmentioning
confidence: 99%
“…67 Burden of care had a positive relationship with age and care duration. 68 Notably, burden decreased to the extent that family caregivers were able to perceive positive and/or negative symptoms. Among the intervention group, their burden gradually decreased even if it was not significantly different from the baseline.…”
Section: Discussionmentioning
confidence: 99%
“…Family caregiving for individuals with mental disorders is a source of burden that has been studied since the psychiatric reform that led to deinstitutionalisation in the early 1980s, when psychiatric care was shifted towards the community, and still receives researchers' attention (Di Lorenzo et al, 2021;Koç et al, 2021;Ribé et al, 2018;Tamizi et al, 2020). This burden differs from other health conditions, as for families it implies not only a deterioration in physical and mental health (Thunyadee et al, 2015) but also stigma (Allerby et al, 2015;Yin et al, 2020) and a perceived lack of information and support from the mental health services (Graneheim and Åström, 2016;Olasoji et al, 2017;Ribé et al, 2018;Cheng et al, 2020;Liu and Zhang, 2020).…”
Section: Introductionmentioning
confidence: 99%